Deterministic upper bounds on performance of generalized processor sharing based on fractal regulators - ZHANG Lian-ming1; CHEN Zhi-gang2; ZHAO Ming2; WANG Lei3 (Tongxin xuebao)
In order to get exact bounds problems encountered in networking with self-similar input traffic,a fractal regu-lator was introduced into the ingress of a generalized processor sharing（GPS） system for regulating the self-similar traf-fic,and a model was presented based on fractal regulator and GPS.The deterministic bounds on queue length,delay,de-lay jitter and effective bandwidth of the system with self-similar input traffic were derived using network calculus.Nu-merical simulations demonstrate that the bound models of a GPS system based on fractal regulators using network calcu-lus are suited for the networks with self-similar input traffic.